The TTIP's impact: bringing in the missing issue - Myant, Martin; O'Brien, Ronan (Brussels, 2015)
"This working paper reviews the main studies on the economic impact of the Transatlantic Trade and Investment Partnership (TTIP) and concludes that benefits are minimal and the TTIP would not get Europe of the crisis. It also looks at the one-sided way regulations are considered only as costs for business in the TTIP with serious implications for the democratic control of such regulations for EU member states. "